Profile of conceptual understranding in subtraction among grade 2 madrasah ibtidaiyah - Muhammad Syahru Romadhon; Irawan, Wahyu Henky; Abdussakir, Abdussakir (Jurnal Bidang Pendidikan Dasar, 2025)
Understanding the concept of subtraction is a critical component of mathematics education at the elementary level, particularly for second-grade students in Madrasah Ibtidaiyah. The objective of this research is to analyze students' understanding of the concept of subtraction through a qualitative approach using an exploratory descriptive method. Data were collected through descriptive tests, interviews, and documentation involving second-grade students of MI Islamiyah. The results revealed a variation in conceptual understanding among students, with some employing formal methods such as stacked counting, while others utilized visual strategies such as line counting. The findings underscore the significance of understanding place value and employing effective subtraction strategies in enhancing students' comprehension. This study concludes that there is a necessity for a more comprehensive learning approach and personalized guidance to facilitate students' thorough mastery of the concept of subtraction